If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4x + -9) + -7 = 5(x + -3) + 38 Reorder the terms: 5(-9 + 4x) + -7 = 5(x + -3) + 38 (-9 * 5 + 4x * 5) + -7 = 5(x + -3) + 38 (-45 + 20x) + -7 = 5(x + -3) + 38 Reorder the terms: -45 + -7 + 20x = 5(x + -3) + 38 Combine like terms: -45 + -7 = -52 -52 + 20x = 5(x + -3) + 38 Reorder the terms: -52 + 20x = 5(-3 + x) + 38 -52 + 20x = (-3 * 5 + x * 5) + 38 -52 + 20x = (-15 + 5x) + 38 Reorder the terms: -52 + 20x = -15 + 38 + 5x Combine like terms: -15 + 38 = 23 -52 + 20x = 23 + 5x Solving -52 + 20x = 23 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -52 + 20x + -5x = 23 + 5x + -5x Combine like terms: 20x + -5x = 15x -52 + 15x = 23 + 5x + -5x Combine like terms: 5x + -5x = 0 -52 + 15x = 23 + 0 -52 + 15x = 23 Add '52' to each side of the equation. -52 + 52 + 15x = 23 + 52 Combine like terms: -52 + 52 = 0 0 + 15x = 23 + 52 15x = 23 + 52 Combine like terms: 23 + 52 = 75 15x = 75 Divide each side by '15'. x = 5 Simplifying x = 5
| y^2+12y=-x^2-4x+16 | | 2p+-14p+16p=-4 | | 4.47=log(X) | | 4z-3z=17 | | 16=5h-9 | | 8/10×=24 | | 2w+8w=10 | | -2(k+2)-(-3k-9)=-7 | | D=v*t | | 27x-10y=15 | | -2x-3.6+0.4=-9 | | 9-2a=9+5 | | 8t+8=7t | | 3x^3=0.75x | | 2*-1-y=-9 | | 14.3=-1.4+3D | | 2*1-y=-9 | | 0=78+8x | | x+8.1=14.5 | | 5n^2+n+6=5 | | 5p-(1)(1-p)=2p+5(1-p) | | 160-15x=100 | | -2u+7x=13 | | 5p-(2)(1-p)=1p+5(1-p) | | 29(x+4)=5(6x-2) | | 17=8-3G | | 20=b/4 | | (2x+3)(x-1)=6x | | 0.0915t^2-0.938t+1.705=0 | | 2.5x^2+10x+15=0 | | 2(4x-9)=7x | | 15(5b+3)= |